Issuance of the European investigation order at the stage of a preparatory proceeding for the purpose of obtaining information constituting bank secrecy - Kąkol, Cezary (Ius Novum, 2023)
The article discusses matters related to the issuance of the European Investigation Order (EIO) during the stage of a preparatory proceeding, the objective of which is to obtain information protected by banking secrecy from a foreign bank. Attention is drawn to the essence of this instrument of international cooperation in criminal matters and its comprehensive nature. A key problem revealed in prosecutorial and judicial practice consists of determining the entity competent to issue the European Investigation Order in the in rem phase of the preparatory proceedings. This issue also necessitates determining whether, in such a procedural situation, it is necessary to obtain the consent of the district court to access information subject to bank secrecy and whether this affects the scope of competence of the court or the prosecutor. An examination of case law and the accompanying opinions of the doctrine presented in the article reveals a non-uniform, even mutually exclusive, approach to this issue. A critical look at the presented range of views enables a clear stance on the aforementioned issues and the formulation of a de lege ferenda proposal.